The COVID-19 SUSPECT DETECTION BASED ON OXYGEN BLOOD LEVELS OF COVID-19 POLTEKAD ELECTRONIC DETECTOR DESIGN WHICH USING PHOTOPLETHYSMOGRAPHY (PPG) METHOD MOVING AVERAGE - Pratama, Ivandhika Bagas; Muda, Nur Rahman Supadmana; Pradani, Erlillah Rizqi Kusuma (Pustaka Poltekad, 2021)
Abstract – Patients with Covid-19 have several symptoms, one of which is a decrease in the oxygen content in the blood or oxygen saturation (SpO2). Detecting oxygen saturation in preventing the spread of Covid-19 is one of the first steps. In this study, researchers conducted an experiment to detect oxygen levels in the blood or oxygen saturation on the POLECTOR C-19 device that was made. By using a photoplethysmography (PPG) which is carried out non-invasively using the sensor, the MAX30102 aim is to get the oxygen saturation value which is used as a reactive and non-reactive decision maker. With the method, the moving average data used from the sensor readings in the form of analog data will be changed using the formula Ratio of Ratios by calculating the average oxygen level then the results can be used to calculate oxygen levels in the blood. The results of sensor readings on the POLECTOR C-19 tool with a digital oximeter from an average value of 10 samples have a difference in value of 0.4, the reading results are the same as the readings of existing medical devices (digital oximeter) so that this tool can be used as a reader. oxygen saturation parameters. In conclusion, this tool can detect a person's condition by predicting the risk or no risk of Covid-19 from the results of the sensor readings of oxygen levels in the blood.